Exploring the Use of Educational Robotics in Non-formal Learning Environments: A Systematic Mapping - Ribeiro, Carlos E.; Trindade, Daniela de F. G.; Palácios, Rodrigo H. C.; Todt, Eduardo (Anais do Workshop de Informática na Escola (WIE); 2023: Anais do XXIX Workshop de Informática na EscolaDO - 10.5753/wie.2023.235277, 2023)
This paper presents a systematic mapping study on the application of educational robotics in non-formal educational settings such as science clubs, museums, libraries, extracurricular activities, and non-governmental organizations (NGOs). The aim of this study is to explore the potential and challenges of educational robotics in these settings, specifically in relation to teaching and learning in Science, Technology, Engineering, Arts, and Mathematics (STEAM) domains. A methodological approach was employed, involving the selection of papers based on specific inclusion and exclusion criteria. Our findings indicate that educational robotics not only fosters computational thinking, problemsolving, creativity, and collaborative skills but also enhances student motivation and self-efficacy. Furthermore, we identify various challenges associated with the implementation of educational robotics in non-formal settings. These insights may serve as a foundation for future research and pedagogical practices in the field.